Determinan Dividen Payout ratio Pada Perusahaan Manufaktur Sektor Aneka Industri Yang Terdaftar Di Bursa Efek Indondesia - Amelia, Maya; Ermalina , Ermalina (Mandiri : Jurnal Akuntansi dan Keuangan, 2022)
This study aims to analyze the Current Ratio, Return On Assets, and Debt To Equity Ratio to the Dividend Payout Ratio of Manufacturing Companies in the Various Industries Listed on the Indonesia Stock Exchange (IDX). In research using descriptive quantitative associative approach, the sample selection in this study used purposive sampling method and obtained 8 companies that match the criteria. The data of this study were obtained from the Indonesia Stock Exchange. The result of this study is the adjusted R-square value of 40.9%. Partially shows that the Current Ratio and Debt To Equity Ratio variables have a positive effect on the Dividend Payout Ratio, while the Return On Assets variable has a negative effect on the Dividend Payout Ratio. Then, the variables Current Ratio, Return On Assets, and Debt To Equity Ratio effect together or simultaneously on the Dividend Payout Ratio.